2016
DOI: 10.1080/02640414.2015.1136069
|View full text |Cite
|
Sign up to set email alerts
|

Association of physical fitness and fatness with cognitive function in women with fibromyalgia

Abstract: This study assessed the association of fitness and fatness with cognitive function in women with fibromyalgia, and the independent influence of their single components on cognitive tasks. A total of 468 women with fibromyalgia were included. Speed of information processing and working memory (Paced Auditory Serial Addition Task), as well as immediate and delayed recall, verbal learning and delayed recognition (Rey Auditory Verbal Learning Test) were assessed. Aerobic fitness, muscle strength, flexibility and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 41 publications
0
7
0
3
Order By: Relevance
“…Soriano-Maldonado et al . also suggested that there is no association between central adiposity and cognitive dysfunction in patients with fibromyalgia 40 . Of the two body composition parameters addressed in this study, there is a consistent association between skeletal muscle and the risk of AD, whereas conflicting results have been observed in studies on the association between obesity and the risk of AD in elderly subjects 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Soriano-Maldonado et al . also suggested that there is no association between central adiposity and cognitive dysfunction in patients with fibromyalgia 40 . Of the two body composition parameters addressed in this study, there is a consistent association between skeletal muscle and the risk of AD, whereas conflicting results have been observed in studies on the association between obesity and the risk of AD in elderly subjects 41,42 .…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the possible mediation of executive dysfunction by overweight, assessment of additional physical and behavioral variables may be informative in future studies. For example, assessments of physical activity, aerobic fitness, waste circumference or body fat may be help to uncover the underlying mechanisms [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies conducted in overweight and obese individuals drawn from the general population showed inverse associations between body mass index (BMI) and cognitive performance [ 40 43 ]. To our knowledge, only a single study has addressed this issue in FMS [ 44 ]. While aerobic fitness correlated positively with memory performance, BMI, percent body fat, fat-mass index and waist circumference showed no effect.…”
Section: Introductionmentioning
confidence: 99%
“…70 Self-reported questionnaires are useful to screen for dyscognition in patients with FM, but full neuropsychological testing may be required to delineate the extent of cognitive dysfunction. 163 In brain functional magnetic resonance imaging (fMRI) studies, 71,170 FM patients showed lower activation in the inhibition and attention networks and increased activation in other areas. Because inhibition and pain perception may use overlapping networks, resources taken up by pain processing may be unavailable for other processes.…”
Section: Common Featuresmentioning
confidence: 99%